MANAJEMEN AMARAH PETUGAS PENGENDALIAN MASSA (DALMAS) POLDA JATIM - Ridwan, Syafiudin (Jurnal Psikologi, 2012)
Anger management has become research area with an increasing interest in the last three decades, particularly which was associated with violence paradigm performed by and toward police officer. The objectives of this study were: 1) to describe the anger management of Dalmas officer, especially in task accomplishment and 2) to explain the dynamic among the anger management components. This study applied grounded theory method of qualitative approach. The data were collected by conducting interviews with 5 Dalmas officers of East Java Police Region. The criteria for participant selection are: 19-25 years of age, attained high score criterion in Novaco’s Anger Scale, had accomplished all kind of Dalmas assignments, with at least one-year experience as Dalmas officers. Data analysis was performed thematically to the verbatim transcribed interviews. The data and theory triangulation had been applied to increase research result credibility. Based on the thematic analysis, found that Dalmas officer’s anger management was composed by various components outlined into four aspects of anger management wich wee interacted each other: the meaning of anger, anger experience recognition, response choosing, and evaluation. The finding revealed several phenomena as the unique characteristics of participants’ anger management, which were: appraisal adjustment, anger coping strategy conditioning, and identification of role and identity in anger management.Keywords: anger management, Dalmas officer